2014
DOI: 10.3390/ijms151221777
|View full text |Cite
|
Sign up to set email alerts
|

Variants of the Low Oxygen Sensors EGLN1 and HIF-1AN Associated with Acute Mountain Sickness

Abstract: Two low oxygen sensors, Egl nine homolog 1 (EGLN1) and hypoxia-inducible factor 1-α inhibitor (HIF-1AN), play pivotal roles in the regulation of HIF-1α, and high altitude adaption may be involved in the pathology of acute mountain sickness (AMS). Here, we aimed to analyze single nucleotide polymorphisms (SNPs) in the untranslated regions of the EGLN1 and HIF-1AN genes and SNPs chosen from a genome-wide adaptation study of the Han Chinese population. To assess the association between EGLN1 and HIF-1AN SNPs and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…Further analyses suggested that the rs12406290–rs2153364 haplotype is linked to AMS+ (Zhang et al . ). We propose that pharmacological means to stabilize PHDs and FIH in hypoxia might be an interesting alternative way for inhibiting the HIF pathway, and thus perhaps prevent the symptoms of AMS, keeping in mind the same cautionary remark made for direct HIF‐1 repression.…”
Section: Potential Drug Targets For Preventing Amsmentioning
confidence: 97%
“…Further analyses suggested that the rs12406290–rs2153364 haplotype is linked to AMS+ (Zhang et al . ). We propose that pharmacological means to stabilize PHDs and FIH in hypoxia might be an interesting alternative way for inhibiting the HIF pathway, and thus perhaps prevent the symptoms of AMS, keeping in mind the same cautionary remark made for direct HIF‐1 repression.…”
Section: Potential Drug Targets For Preventing Amsmentioning
confidence: 97%
“…Of note, there is a high interindividual variability in expression of HIF and HIF target genes following inflammatory or hypoxic stimuli, which at least partially can be explained by genetic variants like single nucleotid polymorphisms. In this context, we have previously shown that additionally to the extent of hypoxic or inflammatory stimuli or their duration, genetic variants in HIF-1, HIF-2, and HIF-degrading PHD-2 alter human adaptation to hypoxia [15][16][17][18][19]. High altitude residents thus have blunted hypoxic ventilatory response and diminished pulmonary hypertension under hypoxia [20,21], increased heart rate, improved peripheral oxygen saturation, and reduced incidence of mountain sickness, as assessed using the Lake Louise Score (LLS) [15,16,[22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…e inhibition of PPARα function may increase organs' susceptibility to oxidative damage [31,32]. Furthermore, HIF1A, HIF1AN, and EGLN1 participate in oxidative stress and the occurrence of metabolic diseases through HIF mediated transcriptional regulatory mechanism [21,[33][34][35]. So, we propose our hypothesis that associations may exist between HIF-related genetic factors and the susceptibility or resistance to HAH in the Chinese Han population.…”
Section: Introductionmentioning
confidence: 83%
“…Genotyping. We selected 35 SNPs in EPAS1, HIF1A, HIF1AN, EGLN1, and PPARA from the dbSNP database (http://www.ncbi.nlm.nih.gov/projects/ SNP/), and several of them had been reported to be associated with high-altitude illness or hypoxia in previous literatures [29,30,33]. SNPs that participated in adaptability adjustment of hypoxia located in noncoding regions more frequently than in coding regions, so we chose SNPs from introns, 3′ or 5′ untranslated regions, and upstream or downstream region of target genes.…”
Section: Snps Selection Andmentioning
confidence: 99%